2019
DOI: 10.1002/jcb.29029
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the long noncoding RNA TRHDE‐AS1 inhibits the progression of lung cancer via the miRNA‐103/KLF4 axis

Abstract: Aim The aim of this study was to explore the role and molecular basis of the long noncoding RNA (lncRNA) TRHDE‐AS1 in lung cancer. Methods We used real‐time polymerase chain reaction to analyze the messenger RNA expression levels of TRHDE‐AS1, miR‐103, and KLF4. The cell viability, proliferation, and invasion rates were assessed via 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide, Cell Counting Kit‐8, and Transwell assays to elucidate the role of TRHDE‐AS1. Results Our results demonstrated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
(43 reference statements)
2
19
0
Order By: Relevance
“…Although the roles of numerous miRNAs in malignant tumors have been reported, little research has revealed the function of miR-103 on tumor progression (41). miR-103 has been reported to have a tumor suppressor effect on NSCLC (42), however, to the best of our knowledge, a comprehensive assessment of the effects of miR-103 on all processes in NSCLC cells has not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the roles of numerous miRNAs in malignant tumors have been reported, little research has revealed the function of miR-103 on tumor progression (41). miR-103 has been reported to have a tumor suppressor effect on NSCLC (42), however, to the best of our knowledge, a comprehensive assessment of the effects of miR-103 on all processes in NSCLC cells has not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC the expression of KLF4 is negatively regulated by various microRNAs: miR-25, miR-103, miR-145 and miR-3120-5p [ 69 , 73 , 74 , 75 ]. KLF4 expression is positively regulated by metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), a long non-coding RNA (lncRNA) that has been demonstrated to function as an oncogene [ 74 ].…”
Section: Lung Cancermentioning
confidence: 99%
“…This regulation is indirect as MALAT1 directly targets miR-145 and in this way it reduces the inhibitory effects of miR-145 on KLF4 activity [ 74 ]. Thyrotropin Releasing Hormone Degrading Enzyme (TRHDE)-Antisense RNA 1 (TRHDE-AS1) is another lncRNA positively regulating the expression of KLF4, and this regulation is most likely mediated by miR-103 [ 75 ]. These findings emphasize the importance of non-coding RNAs in the regulation of KLF4 activity.…”
Section: Lung Cancermentioning
confidence: 99%
“…gov/nuccore/NR_026837). This long non-coding RNA is found in the cytoplasm and binds directly to miR-103 in samples of human lung, inhibiting parameters of human lung cancer progression (Zhuan et al, 2019). Individuals challenged with FIGURE 1 | A map of candidates for transcriptional regulation of Trhde expression predicted by bioinformatic analysis.…”
Section: Trhde Gene Transcripts Protein Structure Isoforms and Spementioning
confidence: 99%